2021
DOI: 10.48550/arxiv.2104.05347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radar SLAM: A Robust SLAM System for All Weather Conditions

Abstract: A Simultaneous Localization and Mapping (SLAM) system must be robust to support long-term mobile vehicle and robot applications. However, camera and LiDAR based SLAM systems can be fragile when facing challenging illumination or weather conditions which degrade their imagery and point cloud data. Radar, whose operating electromagnetic spectrum is less affected by environmental changes, is promising although its distinct sensing geometry and noise characteristics bring open challenges when being exploited for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…In addition, researchers have to spend lots of time and effort to maintain and repair LiDARs installed on the IVs. 4) Fusion-based SLAM: In order to avoid the problems with failures in single sensor or low robustness, fusing multiple modalities data methods have been introduced by researchers including visual-inertial [22][23][24], LiDAR-inertial [25][26][27][28], visual-LiDAR inertial [29][30][31] and other fusion, such as adding sonars [32] or radars [33], SLAM approaches. We found that fusion methods usually introduce IMU data with higher updating frequency to SLAM systems.…”
Section: A Localizationmentioning
confidence: 99%
“…In addition, researchers have to spend lots of time and effort to maintain and repair LiDARs installed on the IVs. 4) Fusion-based SLAM: In order to avoid the problems with failures in single sensor or low robustness, fusing multiple modalities data methods have been introduced by researchers including visual-inertial [22][23][24], LiDAR-inertial [25][26][27][28], visual-LiDAR inertial [29][30][31] and other fusion, such as adding sonars [32] or radars [33], SLAM approaches. We found that fusion methods usually introduce IMU data with higher updating frequency to SLAM systems.…”
Section: A Localizationmentioning
confidence: 99%
“…Surveys on the general SLAM problem can be found in [11], [13], which provide an overview of various techniques, including FastSLAM, GraphSLAM, and belief propagation SLAM [15], [26]- [28]. Initially, R-SLAM was predominantly employed in radar and automotive niche applications [29]- [31]. For instance, in [29], an algorithm utilizing the iterative closest point (ICP) graph method is presented, which matches consecutive scans obtained from a frequency-modulated continuouswave (FMCW) radar along with odometry information.…”
Section: A Related Work and Proposed Contributionmentioning
confidence: 99%
“…Although Radar has its drawbacks, including multipath phenomena, ghost reflections, higher noise levels, and lower accuracy compared to LiDAR, it demonstrates exceptional robustness and is capable of long-range detection and map construction during severe weather conditions. Research in this area has gained significant attention in recent years (Hong et al, 2020(Hong et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%